Novel synergistic fungicidal mixtures of oxathiapiprolin protect sunflower seeds from downy mildew caused by Plasmopara halstedii - Cohen, Yigal (PLoS One, 2019)
Plenaris (oxathiapiprolin) applied to sunflower seedlings was highly effective in controlling downy mildew incited by the oomycete Plasmopara halstedii. In vitro assays revealed strong suppression of zoospore release and cystospore germination of P.halstedii by Plenaris. Bion (acibenzolar-S-methyl) and Apron (mefenoxam) were partially effective when used singly, but performed synergistically when mixed with Plenaris. Seed treatment (coating) with Plenaris provided dose-dependent control of the disease whereas Bion and Apron provided partial or poor control. However, seeds treated with mixtures containing reduced rates of Plenaris and full rates of Bion and/or Apron provided complete control of the disease due to the synergistic interaction between these components. Such mixtures should be used for seed treatment in the field to minimize selection pressure imposed on the pathogen.